Sistem Informasi Buku Tamu Perpustakaan Menggunakan QR Code Berbasis PHP Pada STIKes Syedza Saintika - Muhammad Ihksan; Nurul Abdillah; Arika Juwita Z (Universitas Batanghari Jambi, 2022)
The role of science and technology in all sectors, including education, is now well established. STIKes Syedza Saintika has a comprehensive library and various visiting activities, however at present moment, student visits are still manually documented in the library's visitor book, which takes time to fill out and is still reviewed on a regular basis while performing a summary of the visit. Of course, a manual method is prone to mistakes, but a technology-based library guest book system employing a QR Code is not. Based on the aforementioned issues, a library visitor book system utilizing a QR Code is required, which is projected to reduce mistakes and give ease to students and librarians in processing library visit data. A System Development Life Cycle (SDLC) design is used in this investigation. This study develops a QR Code-based guest book information system for library visits, which aids students and librarians in handling guest book data.